2017
DOI: 10.1111/apt.14451
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: human gut dysbiosis induced by non‐antibiotic prescription medications

Abstract: SummaryBackground: Global prescription drug use has been increasing continuously for decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
136
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(149 citation statements)
references
References 120 publications
3
136
0
10
Order By: Relevance
“…23 Bile acids regulate glucose homeostasis through the activation of nuclear receptors such as the pregnane X receptor, and mount antimicrobial defences via activation of the vitamin D receptor. 24 Statins have been found to influence the human gut microbiome, 25 and remodelling of murine gut microbiota resulted in increased risk of diabetes in mice via pregnane X receptor activation. 26 The clinical implication of gut dysbiosis associated with statins is uncertain as our study could not verify this mechanism.…”
Section: Figurementioning
confidence: 99%
“…23 Bile acids regulate glucose homeostasis through the activation of nuclear receptors such as the pregnane X receptor, and mount antimicrobial defences via activation of the vitamin D receptor. 24 Statins have been found to influence the human gut microbiome, 25 and remodelling of murine gut microbiota resulted in increased risk of diabetes in mice via pregnane X receptor activation. 26 The clinical implication of gut dysbiosis associated with statins is uncertain as our study could not verify this mechanism.…”
Section: Figurementioning
confidence: 99%
“…16s rRNA microbiome analysis of the bacterial community micro-dissected from the biofilm revealed that Gammaproteobacteria, a bacterial class associated with antibiotic induced dysbiosis, are in much lower abundance in the biofilm compared to adjoining areas. In a healthy gut, members of phylum Proteobacteria are normally maintained at very low levels but expand significantly in dysbiosis (Le Bastard et al, 2018; Rivera-Chavez et al, 2017). Increased abundance of class Gammaproteobacteria is seen in metabolic disorders (Larsen et al, 2010; Qin et al, 2012), obesity (Fei and Zhao, 2013; Sen et al, 2017), and inflammatory bowel disease (Gevers et al, 2014), all pathologies characterized by intestinal inflammation (Sen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing prestige of the journal is reflected in the most recent increase in our impact factor (IF); during 2019, our 2‐year IF increased from 7.357 to 7.731 ranking AP&T in 11th place among 84 journals in gastroenterology and hepatology. The 10 papers published during 2018 that were the most highly cited during 2019 included such diverse topics as the epidemiology of Helicobacter pylori infection, the intestinal mirobiome and dysbiosis, biologic agents for IBD and evolving treatments for chronic viral hepatitis.…”
mentioning
confidence: 99%